Floquet stroboscopic divisibility in non-Markovian dynamics. (5th September 2018) - Bastidas, Victor M; Kyaw, Thi Ha; Tangpanitanon, Jirawat; Romero, Guillermo; Kwek, Leong-Chuan; Angelakis, Dimitris G
Abstract: We provide a general description of a time-local master equation for a system coupled to a non-Markovian reservoir based on Floquet theory. This allows us to have a divisible dynamical map at discrete times, which we refer to as Floquet stroboscopic divisibility . We illustrate the theory by considering a harmonic oscillator coupled to both non-Markovian and Markovian baths. Our findings provide us with a theory for the exact calculation of spectral properties of time-local non-Markovian Liouvillian operators, and might shed light on the nature and existence of the steady state in non-Markovian dynamics.